A Simple Method to Control The Excitation Angle for Switched Reluctance Motor - Slamet - Riyadi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
A switched reluctance motor (SRM) has been an alternative solution for electric drives because of its benefit features. The use of such a motor in electric vehicles (EVs) or hybrid electric vehicles (HEVs) requires a control strategy that is capable to develop high torque. SRMs are commonly available in the market with rotor position detectors embedded inside. Problems will appear when such detectors are not symmetrically installed because most of SRM control strategies are commonly based on them. Inaccurate pulses will be generated by the control circuit which finally takes effect on phase current commutation or the beginning of the excitation which is not on proper angle. The use of such detectors is just capable to give information of rotor position in common angles. Improvement for such problems can be done by generating pulses related to the rotor position in smooth angles. In this paper, a control strategy to produce excitation signals with proper angles for SRM stator winding is proposed. By using input capture facility that is commonly available in embedded system, excitation angles can be controlled precisely because a large number of pulses can be produced by the system. Accuracy level of this strategy is determined by TIMER period of embedded system and speed of SRM. To verify the analysis, laboratory experiments were done. They show that the proposed control strategy is capable to rotate the motor with better performance.